Influence of tumor necrosis on treatment sensitivity and long-term survival in nasopharyngeal carcinoma. (February 2021) - Liang, Shao-Bo; Chen, Lu-Si; Yang, Xing-Li; Chen, Dan-Ming; Wang, Dong-Hui; Cui, Chun-Yan; Xie, Chuan-Bo; Liu, Li-Zhi; Xu, Xiang-Ying
Highlights: Tumor necrosis served as a predictor of treatment sensitivity and poor prognosis in patients with nasopharyngeal carcinoma (NPC). Lymph node necrosis significantly improved the prognostic value of the current N classification criteria of NPC. Patients with tumor necrosis might require effective strengthening treatment such as with radio chemotherapy sensitizers. Abstract: Purpose: To assess the impact of tumor necrosis on treatment sensitivity and long-term survival in patients with nasopharyngeal carcinoma (NPC) treated using intensity-modulated radiation therapy (IMRT). Participants and methods: In total, 757 patients with non-metastatic, histologically confirmed NPC were retrospectively examined. All patients were treated using IMRT; 93.7% patients with stage T3-T4/N1-N3 disease also received cisplatin-based chemotherapy. Results: The incidence rates of tumor necrosis in primary tumor, retropharyngeal lymph nodes, neck lymph nodes, and total tumor were 2%, 17.7%, 21.5%, and 31.4%. Overall, 40.8% patients with necrosis of the total tumor achieved complete response (CR) and 54.7% patients without tumor necrosis achieved CR at the end of treatment ( χ 2  = 12.728, P  < 0.001). The estimated 7-year overall survival (OS), failure-free survival (FFS), distant metastasis-free survival (DMFS), and loco-regional relapse-free survival (LRRFS) for patients with tumor necrosis and without tumor necrosis of the total tumor were 68.5% vs. 88.4%, 70.5% vs. 88.1%, 77.6% vs. 90.6%, and 85.9% vs. 91.3%, respectively (all P  < 0.001). Multivariate analyses indicated that necrosis of the total tumor was an independent predictor of OS, FFS, DMFS, and LRRFS. The impact of lymph node necrosis on long-term survival was similar to that of necrosis of the total tumor. ROC curves verified that inclusion of lymph node necrosis improved the predictive value of the current N classification criteria ( P  = 0.006). Conclusions: Tumor necrosis served as a predictor of treatment sensitivity and poor prognosis for patients with NPC. Lymph node necrosis significantly improved the prognostic value of the current N classification criteria for NPC.